جدوى التكامل الاقتصادي المغاربي 1980-2015 - مامون, فاطمة الزهرة; بكوش, زينب; لخويمس, محمد فرج (University of eloued جامعة الوادي, 2017)
تناولتالدراسةالبحثعنمعرفةجدوىالتكاملالاقتصاديلدولالاتحادالمغربالعربيأيىلتتحصل دوللاتحادالمغربالعربيعلىمنافععندقيامىذاالاتحادأولا , حيثتناولنافيالفصلالأولمفاىيمومرتكزاتالتكاملالاقتصادي , وكذاتطرقناإلىتجربةالتكاملالاقتصاديلدولمجلسالتعاونالخليجي , أمافيالفصلالثانيتناولناالاتحادالمغربالعربيوالتكاملالاقتصادي , حيثأىمماتمالوقوفعندهىوأنلاتحادمغربالعربيلوعواملمتشابومنهاالديناللغةوالتاريخ , وتقاربهاالجغرافيوتوفرىاعلىإمكاناتاقتصاديةىائلة، كمااتضحمنخلالىذاالفصلعواملنجاحالتكاملالاقتصاديلدوللاتحادالمغربالعربي, وىيالعواملالاقتصاديةوالغيراقتصاديةالمتوفرةفيدولومنشأنهاتحقيقأسمىدرجةمنالرفاىيةالاقتصادية , والتبادلالتجاري , وتحقيقمعدلاتنموجيدة :The study examined the study of the feasibility of the economic integration of the countries of the Arab Maghreb Union, ie, do the countries of the Arab Maghreb Union get the benefits of this union first, where we discussed the concepts and pillars of economic integration in the first chapter, as well as the experience of economic integration of the GCC countries. The second chapter dealt with the Arab Maghreb Union and economic integration. The most important thing was that the Arab Maghreb Union has similar factors, such as religion, language and history, geographical proximity and availability of enormous economic potential. The economic growth of the countries of the Arab Maghreb Union, the economic and non-economic factors available in its countries, can achieve the highest degree of economic prosperity, trade exchange and achieve good growth rates.
مذكرة ماستر تجارة دولية
Keywords: الاتحادالمغربالعربي ,التكاملالاقتصادي , الإمكانيات , المواردالمتاحة; Arab Maghreb Union, economicintegration, possibilities, availableresources.